Analysis of Factors Affecting Inpatient Satisfaction at Vina Estetika General Hospital Medan - Elvira Hayati (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2023)
Measurement of health service user satisfaction is one indicator to determine the quality of health services. The purpose of the study was to analyze the factors that influence the satisfaction of inpatients at the Vina Estetica General Hospital. The research design was a cross sectional study, the sample was patients who were treated at the Vina Aesthetic Hospital Medan. The research variables were measured using a questionnaire prepared by the researcher and tested for validity and reliability. Analysis of multiple logistic regression test data. The results of the multiple linear regression equation research show that from these five independent variables, there is only one variable that has a positive effect on the dependent variable or patient satisfaction, namely the Physical Evidence variable (Tangibles) with a value of 0.165. Meanwhile, the other four independent variables have a negative effect on the patient satisfaction variable. The regression coefficient for each variable is -0.145 for the Empathy variable, -0.129 for the Reliability variable, then -0.028 for the Responsiveness variable. , and -0.266 for the assurance variable.